FIKIH DAN METODE ISTINBĀṬ IBN HAZM - Taufiqul Hadi (Syarah: Jurnal Hukum Islam & Ekonomi, 2019)
This study describes the relationship of fiqh and istinbāṭ method conducted by IbnHazm. The aim is to see Ibn Hazm's Islamic legal thinking within the framework of theMazhab Al-Zahiri which has been considered literalist and seemingly rigid. In this case,the principle held by Ibn Hazm is based on the consistency of the texts and taking theexplanation of zahir (ẓawāhirun nuṣūṣ) from the Qur'an, Sunnah Rasul, Ijmā’ Sahabara. and al-Dalil. Ibn Hazm rejected takwil which always did not hold on to thenarcissism of the texts, but Ibn Hazm did not forbid the use of figures of speech providedthat there was a sign (qarīnah), in the form of another clear meaning shift. In this case,this shift is considered an "explanation of ẓāhir lafāẓ" (ẓawāhir alfāẓ) not takwil.Judging from his fiqh and istinbath method, it can be concluded that although Ibn Hazmwas a literalist who rejected all models of ijtihād bi al-ra'yi, but when he terminbathedthe law he still could not escape from the logic elements in his ijtihād.Keywords: fikih, Ibn Hazm, istinbath method